2023
DOI: 10.1002/ange.202300605
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Chemo‐ and Regioselective Radical Carbocyanation of 2‐Azadienes for the Synthesis of α‐Amino Nitriles

Abstract: α‐Amino nitriles are versatile structural motifs in a variety of biologically active compounds and pharmaceuticals and they serve as valuable building blocks in synthesis. The preparation of α‐ and β‐functionalized α‐amino nitriles from readily available scaffolds, however, remains challenging. Herein is reported a novel dual catalytic photoredox/copper‐catalyzed chemo‐ and regioselective radical carbocyanation of 2‐azadienes to access functionalized α‐amino nitriles by using redox‐active esters (RAEs) and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…2-Azaallyl anions as versatile precursors of amine syntheses have attracted the interest of organic chemists . Since the pioneering studies of Murphy, Walsh, Chruma, and our group demonstrated 2-azaallyl anions served as super electron donors (SEDs), they have been applied in the construction of C–C bonds through transition-metal-free radical cross-coupling with various electrophiles, which has enabled the synthesis of multifunctional amines (Scheme a) . More recently, we developed the transition-metal-free C­(sp 3 )–H/C­(sp 3 )–H coupling of saturated heterocycles and cycloalkanes with 2-azaallyl anions by a combination of single-electron transfer (SET) and hydrogen atom transfer (HAT) processes (Scheme b) .…”
mentioning
confidence: 99%
“…2-Azaallyl anions as versatile precursors of amine syntheses have attracted the interest of organic chemists . Since the pioneering studies of Murphy, Walsh, Chruma, and our group demonstrated 2-azaallyl anions served as super electron donors (SEDs), they have been applied in the construction of C–C bonds through transition-metal-free radical cross-coupling with various electrophiles, which has enabled the synthesis of multifunctional amines (Scheme a) . More recently, we developed the transition-metal-free C­(sp 3 )–H/C­(sp 3 )–H coupling of saturated heterocycles and cycloalkanes with 2-azaallyl anions by a combination of single-electron transfer (SET) and hydrogen atom transfer (HAT) processes (Scheme b) .…”
mentioning
confidence: 99%